Comprehensive management for the improved outcome of persistent pulmonary hypertension of the newborn in a one-day-old baby girl: a case report - Koentartiwi, Dyahris; Ramadhanti, Ardhanis; Amalia, Najwa (Medical Faculty of Brawijaya University, Indonesia, 2023)
Introduction: Persistent pulmonary hypertension of the newborn (PPHN) is characterized by an increase in pulmonary vascular resistance (PVR), caused by failure of circulatory adaptation within minutes after delivery. Persistent pulmonary hypertension of the newborn (PPHN) can lead to severe respiratory distress and hypoxemia. Newborns with PPHN are at high risk of severe asphyxia and its complications. This study aims to present a comprehensive assessment and treatment of newborn PPHN that might be applicable in any hospital setting. Case description: A one-day-old baby girl came to the emergency room with the chief complaint of cyanosis since birth. The baby was born with oxygen, with pre-ductal and post-ductal differentiation of 5%. The baby showed weak crying movements and inadequate spontaneous breathing, indicating persistent respiratory distress and a chest x-ray revealed pneumonia. The echocardiogram showed a bidirectional secundum, an atrial septal defect, moderate patent ductus arteriosus, and severe pulmonary hypertension. Sputum culture showed Klebsiella pneumoniae (ESBL). Comprehensive management was given to the patient. After several days of hospitalization, the patient was discharged in good condition. Conclusion: PPHN is associated with high morbidity and mortality in newborns. Comprehensive evaluation and management of PPHN and control of any comorbid conditions must be performed to improve patient outcomes.